2019
DOI: 10.1097/pts.0000000000000613
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Built Environment on Patient Falls in Hospital Rooms: An Integrative Review

Abstract: Objectives:The aims of this study were to identify and evaluate scientific evidence examining the impact of the built environment on patient falls in hospital rooms.Methods: An integrative review (IR) with a systematic literature search was performed using the patient, intervention, comparison, outcome framework. We searched CINAHL, PsychINFO, PubMED, and Web of Science databases. The search included peer-reviewed studies from 1990 to 2017 written in English. An additional hand search was also conducted. Selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The built environment is a core aspect of patient safety, falls risk, 8,20 and potentially also may influence positively or negatively the need for bed moves. Changes to ward layout or practice that can accommodate increased visibility for patients with high falls risk, for example, through decentralized nursing or portable nursing stations, 36 may reduce risk of falls, and the need for bed moves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The built environment is a core aspect of patient safety, falls risk, 8,20 and potentially also may influence positively or negatively the need for bed moves. Changes to ward layout or practice that can accommodate increased visibility for patients with high falls risk, for example, through decentralized nursing or portable nursing stations, 36 may reduce risk of falls, and the need for bed moves.…”
Section: Discussionmentioning
confidence: 99%
“…A recent integrative review highlighted the importance of the built environment in hospitals as a contributor to falls risk, but that there is limited research quantity and quality to adequately inform healthcare design decision-making. 20 Further research needs to focus on design elements for hospital room and wards that can be implemented to achieve improved organisational, staff and patient outcomes, 8 including reduced falls and reduced bed moves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copeland and Chambers (2017) found that the presence of handrails and non-slippery floor covering contributed to a 55% reduction in patient falls [77]. Pati et al (2021) found that the toilet seat on the side wall instead of directly opposite the bathroom entrance is a factor reducing falls [78]. Bosia et al (2016) suggested that oncology and internal medicine departments care about patients and their relatives, their mobility, the ability to move around the room, and easy access to the bathroom.…”
Section: )Infection Controlmentioning
confidence: 99%
“…Although these appraisal tools have been instrumental in evaluating studies involving systematic literature reviews in the field of healthcare design research (e.g., Pati et al, 2019; Weerasuriya et al, 2019), they have shortcomings that needs to be addressed to render more effective and meaningful appraisal of published studies in the domain of healthcare design research. These shortcomings are discussed in the following sections.…”
mentioning
confidence: 99%